2002
DOI: 10.1177/002204260203200403
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Interviewing and Relapse Prevention for DWI: A Pilot Study

Abstract: Driving while impaired is a serious national health problem, and there is a need to develop effective treatments for persons arrested for Driving While Intoxicated (DWI). Motivation for changing substance use behaviors may be critical for avoiding further infractions. Once motivated, the client may more readily develop skills that enhance efficacy to cope with situations leading to DWI. Motivational Interviewing (MI; Miller & Rollnick, 1991) was delivered to DWI-involved clients to enhance motivation to ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
11
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 28 publications
2
11
0
1
Order By: Relevance
“…For example, one pilot study of mandated DWI offenders revealed that those who participated in a BMI pre-treatment group were more likely to complete treatment than those who did not (Lincourt et al, 2002), though the lack of random assignment left unclear BMI's causal role. Other published reports have indicated positive effects when BMI was incorporated into existing DWI intervention programs (Marques et al, 1999;Stein and Lebeau-Craven, 2002;Woodall et al, 2007). With few exceptions (e.g., Chanut et al, 2008) however, inferences about BMI's efficacy in DWI are mostly limited to offenders in a clinical setting, and ⁄ or when BMI is provided in combination with other intervention content.…”
mentioning
confidence: 99%
“…For example, one pilot study of mandated DWI offenders revealed that those who participated in a BMI pre-treatment group were more likely to complete treatment than those who did not (Lincourt et al, 2002), though the lack of random assignment left unclear BMI's causal role. Other published reports have indicated positive effects when BMI was incorporated into existing DWI intervention programs (Marques et al, 1999;Stein and Lebeau-Craven, 2002;Woodall et al, 2007). With few exceptions (e.g., Chanut et al, 2008) however, inferences about BMI's efficacy in DWI are mostly limited to offenders in a clinical setting, and ⁄ or when BMI is provided in combination with other intervention content.…”
mentioning
confidence: 99%
“…Client Satisfaction Questionnaire (CSQ)-Both adolescents and their parents filled out a CSQ during the posttreatment assessment. This CSQ has been used in previous addictions research (see Stein & Lebeau-Craven, 2002). Item content included: "Was it worth your effort to be in this session today?"…”
Section: Peer Behavior Measures: Peer Social Skills and Parent Beliefmentioning
confidence: 99%
“…For example, a pilot study of DWI offenders mandated to treatment revealed that those who participated in an MI pretreatment group were more likely to complete treatment than those who did not (Lincourt, Kuettel, & Bombardier, 2002), although the lack of random assignment left unclear MI's causal role. Other published reports have suggested positive effects when MI was imbedded into existing DWI or other intervention programs (Marques, Voas, Tippetts, & Beirness, 1999;Stein et al, 2006;Stein & Lebeau-Craven, 2002;Woodall, Delaney, Kunitz, Westerberg, & Zhao, 2007). These studies did not address MI's unique contribution to outcome however.…”
Section: Introductionmentioning
confidence: 96%